Ameliorative effect of vitamin E on trichloroethylene-induced nephrotoxicity in rats - Mojgan Heydari; Massumeh Ahmadizadeh; Kambiz Ahmadi Angali (Journal of Nephropathology, 2017)
Background: 1,1,2-Trichloroethylene (TCE) is an important organic solvent which is widespread in the environment. Work place exposure to TCE has been associated adverse effects in many organs including kidney. Vitamin E is an antioxidant that can overcome oxidative stress. Objectives: The aim of the present study is to examine the role of vitamin E against destructive effects of TCE on rat kidney. Materials and Methods: A total of 35 male Wistar rats were randomly divided into seven groups of equal number in each. The rats in group I were the controls received vehicle only. Animals in groups III, V and VII received intraperitoneal injection (i.p) of corn oil. Rats in groups of II, IV, and VI were received vitamin E at a dose of 200 mg/kg; 30 minutes later, animals were received TCE (i.p) at doses of 1000 mg/kg (groups II and III), 1500 mg/kg (groups of IV and V), and 2000 mg/kg (groups of VI and VII) respectively. The experiment repeated for 7 consecutive days. Twenty-four hours after last administration, animals were killed with overdose of sodium pentobarbital. Blood samples were analyzed for blood urea nitrogen (BUN) and creatinine (Cr). One part of the kidney tissues were excised for measuring malondialdehyde (MDA) and glutathione (GSH) concentrations. Another part were excised for histopathological estimation. Results: TCE induced a dose-dependent elevation in BUN, Cr, MDA and markedly decreased GSH level when compared to those in control rats. TCE-induced dose-dependent injury in rat kidney tissue. Vitamin E significantly decreased BUN, Cr, MDA and increased GSH levels and protected kidney damage in TCE treated animals. Conclusions: The observations suggest that vitamin E may have a protective effect against TCE-induced oxidative stress in the rat kidney.